Structural dynamics and economic growth - Arena, R. (Richard); Porta, Pier Luigi (Cambridge : Cambridge University Press, 2011)
Ever since Adam Smith, economists have been preoccupied with the puzzle of economic growth. The standard mainstream models of economic growth were and often still are based either on assumptions of diminishing returns on capital with technological innovation or on endogenous dynamics combined with a corresponding technological and institutional setting. An alternative model of economic growth emerged from the Cambridge School of Keynesian economists in the 1950s and 1960s. This model - developed mainly by Luigi Pasinetti - emphasizes the importance of demand, human learning and the growth dynamics of industrial systems. Finally, in the past decade, new mainstream models have emerged incorporating technology or demand-based structural change and extending the notion of balanced growth. This collection of essays reassesses Pasinetti's theory of structural dynamics in the context of these recent developments, with contributions from economists writing in both the mainstream and the Cambridge Keynesian traditions and including Luigi Pasinetti, William Baumol, Geoffrey Harcourt and Nobel laureate Robert Solow.
Introduction: structural dynamics and contemporary growth theory / Richard Arena and Pier Luigi Porta -- Part I. Structural Dynamics: Past and Present: 1. Structural change: some historical aspects of Pasinetti's work with special reference to classical economics / Peter D. Groenewegen; 2. Structural dynamics in an historical perspective / Mario Pomini; 3. Two approaches to the study of structural change and economic development: Kuznets and Pasinetti / Moshe Syrquin; 4. Analyzing knowledge flows by means of vertical integration / Önder Nomaler and Bart Verspagen; 5. Growth: towards a structural endogenous macro-model / William J. Baumol -- Part II. Structural Dynamics: The Cambridge Keynesian Perspective: 6. Luigi Pasinetti: the senior living heir of the Cambridge School of Economics and the last of the great system-builders / Geoffrey Harcourt; 7. Toward a synthesis in post-Keynesian economics in Luigi Pasinetti's contribution / Heinrich Bortis; 8. Growth theory, structural dynamics and the analysis of consumption / Davide Gualerzi; 9. Luigi Pasinetti's structural economic dynamics and the employment consequences of new technologies / Harald Hagemann; 10. The concept of 'natural economic system': a tool for structural analysis and an instrument for policy design / Roberto Scazzieri; 11. Structural change and invariable standards / Takashi Yagi -- Part III. Epilogue: Structural Dynamics as Part of the 'Unfinished Revolution': On Pasinetti and the unfinished Keynesian revolution / Robert M. Solow; First afterword: Pasinetti on structural dynamics / Robert M. Solow; Growth and structural change: perspectives for the future / Luigi L. Pasinetti; Second afterword: the significance of structural economic dynamics / Luigi L. Pasinetti.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Pasinetti, Luigi L. -- Political and social views; Economic development; Sustainable development